Role of enthalpy and entropy in moisture sorption behavior of pineapple pulp powder produced by different drying methods - Vigano, Juliane [UNESP]; Azuara, Ebner; Telis, Vania R. N. [UNESP]; Beristain, Cesar I.; Jimenez, Maribel; Telis-Romero, Javier [UNESP] (Elsevier B.V., 2012)
Sorption mechanisms of pineapple powders produced by vibro-fluidized drying (VFD), spray drying (SD), freeze drying (FD) or vacuum drying (VD) were interpreted through enthalpy/entropy variations with respect to equilibrium moisture content (EMC) at 20, 30, 40 and 50 degrees C and water activity (a(w)) between 0.059 and 0.907. Powders from SD and VFD were more hygroscopic and integral properties indicated higher stability at changing a, compared to powders from VD and FD. Powders showed an enthalpy driven zone with equal isokinetic temperature (T-BI = 499.0 +/- 4.8 K) due to their same composition, and an entropy controlled zone with different isokinetic temperature, T-B2 (VD: 116.0 +/- 40.6 K; FD: 118.3 +/- 24.1 K; SD: 95.8 +/- 23.4 K; VFD: 81.8 +/- 6.3 K), caused by different microstructures resulting from different drying methods. Powders from SD and VFD presented larger entropic zones that shifted the minimum integral entropy to higher a(w), improving storage stability. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Pineapple pulp powder; Drying methods; Water activity; Sorption isotherm; Thermodynamic properties